Concussion induces focal and widespread neuromorphological changes. (22nd May 2017) - Sussman, Dafna; da Costa, Leodante; Chakravarty, Mallar M.; Pang, Elizabeth W.; Taylor, Margot J.; Dunkley, Benjamin T.
Highlights: Single concussion associated with reduced white, grey matter and total cortical volume. Cortical thinning, primarily in left frontal areas, also observed. No differences were observed in the cerebellum or subcortical structures. A single concussion induces measurable changes in brain structure. Changes manifest as diffuse and local patterns of altered neuromorphometry. Abstract: Concussion induces transient, and oftentimes chronic, lingering impairment to mental functioning, which must be driven by some underlying neurobiological perturbation – however, the physical changes related to sequelae are difficult to detect. Previous imaging studies on concussion have focused on alterations to cortical anatomy, but few have examined the cerebrum, subcortex, and cerebellum. Here, we present an analysis of these structures in a single cohort (all males, 21 patients, 22 controls) using MRI and diagnosed with a single-concussive episode in the acute and sub-acute stages of injury. Structural images were segmented into 78 cortical brain regions and 81, 924 vertices using the CIVET algorithm. Subcortical volumetric analyses of the cerebellum, thalamus, globus pallidus, caudate and putamen were conducted following segmentation. Participants with concussion were found to have reduced white and grey matter volume, total cortical volume, as well as cortical thinning, primarily in left frontal areas. No differences were observed in the cerebellum or subcortical structures. In conclusion, just a single concussive episode induces measurable changes in brain structure manifesting as diffuse and local patterns of altered neuromorphometry.